Chronic respiratory diseases and quality of life in elderly nursing home residents - Carreiro-Martins, Pedro (Chron Respir Dis, 2016)
Few studies have assessed the quality of life (QOL) related to chronic respiratory diseases in the elderly. In the framework of the geriatric study on the health effects of air quality in elderly care centers (GERIA) study, a questionnaire was completed by elderly subjects from 53 selected nursing homes. It included various sections in order to assess respiratory complaints, QOL (World Health Organization QOL (WHOQOL)-BREF), and the cognitive and depression status. The outcome variables were the presence of a score lower than 50 (<50) in each of the WHOQOL-BREF domains (physical health, psychological health, social relationships, and environmental health). Chronic bronchitis, frequent cough, current wheezing, asthma, and allergic rhinitis were considered as potential risk factors. The surveyed sample was (n = 887) 79% female, with a mean age of 84 years (SD: 7 years). In the multivariable analysis, a score of <50 in the physical domain was associated with wheezing in the previous 12 months (odds ratio (OR): 2.03, confidence interval (CI): 1.25–3.31) and asthma (OR: 1.95, CI: 1.12–3.38). The psychological domain was related with a frequent cough (OR: 1.43, CI: 0.95–2.91). A score of <50 in the environmental domain was associated with chronic bronchitis (OR: 2.89, CI: 1.34–6.23) and emphysema (OR: 3.89, CI: 1.27–11.88). In view of these findings, the presence of respiratory diseases seems to be an important risk factor for a low QOL among elderly nursing home residents.